Price Transmission and Distributional Dynamics in Bangladesh’s Vegetable Markets: Evidence from Farm to Retail Levels - Md. Shadikur Rahaman; Md. Ruhul Amin (Indonesian Journal of Social Economics and Agricultural Policy (IJSEAP), 2026)
This study aims to identify the key actors and structural factors contributing to price volatility in Bangladesh’s vegetable supply chain. It specifically examines unjustifiable increases in vegetable prices, despite their essential role in ensuring nutritional balance and meeting daily dietary requirements. To address the research objectives, the study adopts a mixed-methods approach, integrating both qualitative and quantitative data. Primary data were collected in Bogura between January 2024 and May 2025 through structured questionnaires, key informant interviews (KIIs), and focus group discussions (FGDs). In addition, policy documents and official market price notifications were systematically reviewed. The findings reveal that commonly consumed vegetables experience higher levels of price fluctuation at both wholesale and retail stages. Within the actor factor framework, wholesalers, retailers, and intermediaries play a dominant role in driving price escalation. These actors exploit regulatory loopholes, weak market oversight, and limited institutional accountability to maximise profits. The study also identifies corruption involving both government officials and private market actors particularly wholesalers and traders as a critical contributor to persistent price distortions. Furthermore, ineffective traditional market management regulations have undermined the enforcement capacity of the Directorate of National Consumer Rights Protection. Based on these findings, the study proposes the development of a comprehensive policy framework that strengthens market regulation, enhances transparency, and ensures institutional accountability. Such reforms are essential to reducing unpredictable and unjustified price increases, while safeguarding consumer rights and overall welfare.